Puja Mandala South Kuta Learning Video Media Based on Tolerance for Social Studies Content for Fourth-Grade Elementary School Students - Saputra, I Kadek Hendra Dwi; Sujana, I Wayan; Wulandari, I Gusti Agung Ayu (Jurnal Pendidikan Multikultural Indonesia, 2023)
Students in elementary school tend to find it difficult to think abstractly, and the lack of utilization of learning media in the learning process causes students to feel bored and have difficulty understanding the material. This research aims to create learning media through learning videos for fourth-grade elementary school students. The model used in this research uses the ADDIE development model. Observation, interviews, questionnaires/ surveys, and tests were carried out as data collection methods. The subjects in this study consisted of 4 experts and 19 fourth-grade students in elementary schools. Data were analyzed using inferential statistical techniques. The results obtained from the design expert test assessment were 90% (very good), the subject content expert test was 90% (very good), the instructional design expert test was 90% (very good), the learning media expert test was 90% (very good), the individual trial was 90.83% (very good), and small group trial was 90.83% (very good). The results of the effectiveness test, the t-count value is 6,497 with a t-table at the 5% significance level of 2,021. These results show that the t-count is greater than the t-table, meaning there is a significant increase between before and after learning video media. The development of Puja Mandala learning video media based on tolerance is effectively applied to religious diversity in Indonesian social studies content of fourth-grade elementary school students.